Advances in the probiotic production, innovation, and therapeutic applications in health and nutrition - Sultan, Hafiz M.; Fatima, Maria; Rehman, Baqa U.; Sajid, Tehseen; Riaz, Maria; Mustafa, Faizan E.; Hassan, Sania; Imran, Syeda A. (Trends in Infection and Global Health, 2024)
Microorganisms have long been used to produce primary and secondary metabolites essential for human health and environmental sustainability. Due to their rapid growth and reproduction rates, as well as their ability to undergo genetic modifications, microorganisms play a critical role in the manufacturing industry. Probiotics, which are non-pathogenic microorganisms, have gained significant interest due to their various health benefits, including treating vitamin deficiencies, alleviating digestive disorders, enhancing immunity, and detoxifying harmful substances. Probiotics are commonly used to address gastrointestinal issues such as inflammatory bowel disease, as well as conditions like obesity, diabetes, constipation, and colon cancer. Despite these applications, recent advancements in understanding the role of probiotics in managing these diseases have been limited. This review presents the latest insights into probiotics' role in health management. With the growing global population, researchers are focusing on strategies to meet the increasing demand for probiotics. Using advanced techniques, scientists are exploring probiotic strains that can be produced industrially and utilized to treat various medical conditions. This review compiles essential information for probiotic researchers, covering strain selection, production, and applications.